Processus d’altérisation de l’obeah à Sainte-Lucie - Meudec, Marie (Anthropologica, 2015)
The analysis of the processes of stigmatization against obeah in St. Lucia is conducted from the point of view of the negative moralization of "witchcraft." The concept of Othering is useful to the understanding of this phenomenon—both in terms of colonial, religious, popular, media and scientific discourses—and it becomes essential to grasp the social and moral differentiation that these practices and people associated with them are facing. The reception of Othering must also be part of the analysis, through the study of ordinary ethics and strategies of legitimation of practitioners of / or associated with obeah. This perspective demonstrates the need to develop the production of Otherness both as an internalizing and externalizing process.